T/V Distinction in Second Language Acquisition: a case study of chinese mandarin and european portuguese - Zhang, Yuxiong (The ESPecialist, 2025)
The T/V distinction refers to the use of different second-person pronouns to signal social relationships, such as familiarity, respect, or formality, a phenomenon common in many languages, including Chinese Mandarin and European Portuguese. Modern European Portuguese has lost its traditional V-form, with younger generations often using você to express formality and seniority. In contrast, the younger generations often using você to express formality and seniority. In contrast, the posteriorly developed V-form nin has been well preserved and remains frequently used in Chinese Mandarin. This study investigates whether learning a foreign language influences speakers’ choices of address forms in their first language and examines cross-linguistic associations in pronoun use. Three experiments were conducted to examine the influence of a first language on a second language, the reverse influence of a second language on a first language, and the differences in address form preferences between Chinese and Portuguese speakers. Quantitative and qualitative analyses show that learning a foreign language does not effectively influence speakers’ decisions regarding pronoun usage in their first language. Learners tend to establish a direct association between pronoun usage in the two languages. For instance, Chinese speakers generally favor the V-form in most contexts, except when addressing friends or peers of the same age. In contrast, Portuguese speakers consider factors such as formality of the context, age, social relationships, respectfulness, and social status when choosing address forms.